The Role of Organizational Commitment in Mediating the Influence of Transformational Leadership and Work Discipline on Employee Performance in the Public Welfare Section of the Regional Secretariat Manokwari Regency - Reynaldo Charles de Septin DUWIRI; Putu Ngurah Suyatna YASA; Ida Bagus Udayana PUTRA (PT Keberlanjutan Strategis Indonesia, 2025)
Employee performanceis a crucial aspect in determining the success of public sector organizations. Factors such as transformational leadership, work discipline, and organizational commitment play a significant role in shaping employee work behavior. Therefore, analyzing the relationship among these variables is essential for understanding sustainable performance improvement strategies. This study aims to analyze the role of organizational commitment in mediating the influence of transformational leadership and work discipline on employee performance at the Welfare Division of the Regional Secretariat of Manokwari Regency. The entire population of 42 employees was used as the sample through a saturated sampling technique. Data analysis employed the SEM-PLS approach. The results indicate that both transformational leadership and work discipline have a positive and significant effect on employee performance. Transformational leadership also significantly affects organizational commitment, while the effect of work discipline on commitment is not significant. Organizational commitment is proven to significantly influence employee performance and serves as a partial mediator in the relationship between transformational leadership and work discipline on performance. The practical implication is that performance improvement can be achieved through the development of individual KPIs, strengthening discipline through integrated digital attendance systems and clear standard operating procedures (SOPs), as well as fostering a fair work environment to build employee commitment.